PERAN PENDIDIK KRISTEN DALAM PENCEGAHAN KENAKALAN REMAJA DALAM MENYONGSONG MASYARAKAT 5.0 - Lenda Dabora J.F. Sagala; Thia Monika; Elsha Triani Ibi Desi (SAINT PAUL'S REVIEW, 2022)
The lives of today's teenagers determine the future of a nation because teenagers are the nation's future assets. However, recently juvenile delinquency behavior is often very concerning. Amid this situation, the role of Christian educators is very much needed to foster and guide teenagers so that they have good character. The formulation of the problem in this paper is what is the role of Christian religious teachers in the church in preventing juvenile delinquency? So the purpose of this study was to determine the role of Christian religious teachers in the church in preventing juvenile delinquency. This study uses a library research approach. From this research, the results are, first, Christian educators play a role in implementing Christian hospitality. This means that Christian educators should love teenagers and make it happen by providing motivation and encouragement to teenagers to become good people. Second, play a role in conducting counseling guidance. Counseling carried out on adolescents is expected to provide true knowledge about God and satisfaction in receiving the counseling service. Third, play a role in developing youth talents. Because of this role, teenagers can develop the talents that exist in themselves and teenagers can do more positive and good activities. Fourth, make discipleship of the youth. Because teenagers must be guided to stay centered on God.